Glaucoma and Alzheimer Disease: One Age-Related Neurodegenerative Disease of the Brain - Mancino, Raffaele; Martucci, Alessio; Cesareo, Massimo; Giannini, Clarissa; Corasaniti, Maria T.; Bagetta, Giacinto; Nucci, Carlo (Current Neuropharmacology, 2018)
Background: Open Angle Glaucoma (POAG) is the leading causes of irreversible blindness worldwide. Elevated intraocular pressure is considered an important risk factor for glaucoma; however, a subset of patients experiences a progression of the disease even in presence of normal intraocular pressure values. This implies that risk factors other than intraocular pressure are involved in the pathogenesis of glaucoma. A possible relationship between glaucoma and neurodegenerative diseases such as Alzheimer Disease has been suggested. In this regard, we recently described a high prevalence of alterations typical of glaucoma, using Heidelberg Retinal Tomograph-3, in a group of patients with Alzheimer Disease. Interestingly, these alterations were not associated with elevated intraocular pressure or abnormal Central Corneal Thickness values. Alzheimer Disease is the most common form of dementia with progressive deterioration of memory and cognition. Complaints related to vision are common among Alzheimer Disease patients. Methods: In this paper researches related to glaucoma and Alzheimer disease are reviewed. Results: Diseases characteristics, i.e. common features, risk factors and pathophysiological mechanisms gathered in the recent literature do suggest that Alzheimer Disease and glaucoma can be considered both age-related neurodegenerative diseases that may co-exist in the elderly. Conclusion: In conclusion, preclinical and clinical evidence gathered so far support the notion that glaucoma is a widespread neurodegenerative condition whose common pathogenetic mechanisms with other diseases, i.e. Alzheimer Disease, should be further investigated as they may shed new light on these diseases improving both diagnosis and treatments.
Keywords: neurodegeneration